The Dispute Settlement System of Investment in The ASEAN Comprehensive Investment Agreement (ACIA) Framework and The Implications for Indonesia - Delfiyanti, Delfiyanti (Indonesian Journal of International Law, 2022)
In order to implement the ASEAN single market on free flow of investment in the region, the delegations of ASEAN member states signed the ASEAN Comprehensive Investment Agreement (ACIA) on February 26th, 2009 in Cha-am, Thailand. Based on Article 1 (a) and Article 2 of the ACIA Agreement on the objectives of ACIA formation; the legal arrangements for foreign direct investment in this Agreement adhere to an investment regime—“a Free and Open Investment Regime” to achieve the ultimate purpose of economic integration in the ASEAN Economic Community. By implication of the Agreement, Indonesia should attempt to complement the investment legal arrangements in accordance with ACIA regulation. Based on analysis result of Act No. 25 of 2007 on Investment any several provisions are in line with the ACIA although any differences and improvement required. As regard the dispute settlement, both through the ACIA Agreement and the Indonesian Investment Law, there are 2 mechanism channels, the non-legal route (conciliation/negotiation) and the legal (court/arbitration). The option of dispute settlement by the mechanism depends on the concerned parties. Obviously, both of them regulate the legal protection for investors and national security where they belong.